U.S. States’ COVID-19 physical distancing policies and working-age adult mental health outcomes - Shannon M. Monnat; David C. Wheeler; Emily Wiemers; Yue Sun; Xinxin Sun; Douglas A. Wolf; Jennifer Karas Montez (Preventive Medicine Reports, 2023)
In the early months of the COVID-19 pandemic, states enacted multiple policies to reduce in-person interactions. Scholars have speculated that these policies may have contributed to adverse mental health outcomes. This study examines potential associations between states’ COVID-19 physical distancing policies and working-age (18–64) adults’ self-reported mental health. Mental health outcomes (depression, anxiety, worsened mental health, and sought treatment for anxiety or depression) are from the National Wellbeing Survey collected from working-age adults in the United States (U.S.) February 1 to March 18, 2021 (N = 3,804). Data on 12 state policies are from the COVID-19 U.S. State Policy Database. Analyses included logistic regression and Bayesian group index modeling, which identified sets, or “bundles,” of policies that were associated with each mental health outcome. Multiple policies (both separately and in bundles) were associated with adverse mental health outcomes, with certain policies (closures and curfews on retail and other businesses) being particularly important. A one-month increase in exposure to respective model-derived physical distancing policy bundles was associated with a 36% increase in the odds of reporting that COVID-19 worsened one’s mental health (odds ratio [OR] = 1·36; 95% credible interval [CRI] = 1·01 to 1·80), a 6% increase in the odds of meeting the clinical threshold for anxiety (OR = 1·06; CRI = 0·99 to 1·16), and a 15% increase in the odds of seeking treatment for anxiety or depression (OR = 1·15; CRI = 1·02 to 1·49). To accurately understand the role of states’ COVID-19 policies on mental health during the pandemic, researchers must consider how collections of policies might influence outcomes.